Preliminary Free Radical Scavenging, Brine Shrimp Lethality, Antimicrobial and Thrombolytic Activities of Aganosma dichotoma (Roth) K. Schum. - Dey, Sanjoy Chandra; Khan, Mohammd Firoz; Rahman, Mohammad S; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2015)
Bangladesh is a good repository of natural products. Numerous plants are available to facilitate the traditional treatments. Proper scientific evaluations are essential to explore the plant derived drugs. With this view, the crude methanol extract of leaves of Aganosma dichotoma (Roth) K. Schum. and its Kupchan fractions were screened for free radical scavenging, brine shrimp lethality, antimicrobial and thrombolytic activities. Among all extractives, the chloroform soluble fraction demonstrated the highest free radical scavenging activity with IC50 value 18.21 ?g/ml. Moreover, the chloroform soluble fraction showed significant brine shrimp lethality having LC50 value of 3.98 ?g/ml. On the other hand, the petroleum ether, carbon tetrachloride and chloroform soluble materials revealed mild to moderate antimicrobial activity with the zone of inhibition ranging from 7 to 14 mm. In the thrombolytic assay, the carbon tetrachloride soluble partitionate showed the highest clot lysis (30.48%). This is the first report of the comprehensive investigations of different extractives of A. dichotoma for the abovementioned bioassays. DOI: http://dx.doi.org/10.3329/bpj.v17i2.22337 Bangladesh Pharmaceutical Journal 17(2): 177-181, 2014